Advanced fiber optics concepts and technology / Luc Thévenaz, editor. - Thévenaz, Luc (Engineering sciences. Electrical engineering., 2011)
This book provides a comprehensive treatment of the field of modern fiber optics, beginning with the basics of the field summarized in an introductory chapter. Expert contributors then topics such as polarization effects in optical fibers; photonic crystal fibers; highly-doped optical fibers; non-linear effects; amplification and lasing in optical fibers; supercontinuum generation, Rayleigh and inelastic scattering with applications to sensing; optical fiber point sensors, and polymer optical-fiber-based sensors.